RELASI ANTARA ISLAM, NEGARA, PLURALISME, DAN PRIBUMISASI DALAM KACA MATA GUS GUR - Zulyadain, Zulyadain (Tasamuh: Jurnal Studi Islam, 2015)
This article will truly discourse Abdurrahman Wahidâs prominent thinking or ideas like Islam and state, Pluralism, Democracy and Pribumization. These thinkings will be presented in this article. So, based on the these commands, these matters will formulate; (1) Is Neo-modernism Abdurrahman Wahidâs thinking able to said as transformation from the modernism and or traditionalism thinkings? (2) How does socialism-democracy Gus Durâs thinking as ideology of Islam? (3) And how does Islamic Universality Gus Durâ thinking, which views Islam as universal thinking in social life? This research finds that Abdurrahman Wahid always interprets religion as substantial. The type of Gus Durâs thinking who has created four actual views are; Islam and state, Pluralism, Democracy, and Pribumisation of Islam.